Communications Biology - Rosenthal, Christina Karlsson; SpringerLink (Online service) (London : Nature Publishing Group UK : Imprint: Nature Portfolio.)
Communications Biology is an open access journal from Nature Portfolio publishing high-quality research, reviews and commentary in all areas of the biological sciences. Research papers published by the journal represent significant advances bringing new biological insight to a specialized area of research. We also aim to provide a community forum for issues of importance to all biologists, regardless of sub-discipline. The scope of the journal includes all of the basic biological and biomedical sciences. Primary research published in Communications Biology includes novel experimental results, secondary data analysis and innovative experimental and computational methods. We also consider submissions from adjacent research fields where the central advance of the study is of interest to biologists, for example, chemical biology, biophysics and biomedical engineering. The submission and review processes are managed by our in-house professional editors supported by our Editorial Board Members, who provide technical expertise across the breadth of the life sciences. We are committed to rapid dissemination of important research results. Articles are published on a continuous basis with minimal time from acceptance to publication.
Keywords: Life sciences; Life Sciences